Supply chain and local in-transit handling of ‘Carabao’ mango from Davao City to Laguna, Philippines - Bayogan E.V.; Morales W.L.A.; Secretaria L.B.; Franco R.K.G.; Palenzuela M.J.B.; Urquiola M.A.J. (CGIAR, 2023)
Mango (Mangifera indica L.) is a tropical fruit with a unique flavor and high nutritional benefits. It is considered the most important fruit crop in the country based on its high export volume and value, next to banana and pineapple (Department of Agriculture, 2013). The 'Carabao' mango, also known as the 'Super Manila' mango, is a popular variety in the international market. Over the years, there has been an increase in demand for mangoes. However, the Philippines is facing challenges in consistently delivering high quality mangoes to major markets. These challenges are due to various factors such as pests, diseases, poor pre- and post-harvest management, and gaps in the supply chain (PCAARRD-DOST, 2019). Despite the availability of some technologies to reduce production problems in mango, technology adoption remains low. Various technologies, including hot water treatment (HWT), have been studied to improve the quality of mangoes. HWT is a postharvest treatment to control important postharvest diseases such as anthracnose and stem end (Mansour et al., 2006; Le et al., 2010). Heat treatments (HWT 52-55°C, 5 min; and rapid HWT 59-60°C, 35-60 sec) in ‘Carabao’ mango controlled the incidence of anthracnose and stem end rot (Pasilan et al., 2020; Esguerra, 2006). Despite the benefits of HWT, adoption of the technology in the country is very limited to fresh fruit exporters and processors. (Esguerra et al., 2006). An in-transit handling trial was conducted to gain a better understanding of the conditions and quality of mangoes along the local supply chain with the use of hot water treatment. This study monitored the conditions and assessed the quality of mangoes during transit.